Hutang Piutang Dana Kas Masjid Dengan Tambahan Pembayaran Perspektif Hukum Ekonomi Syariah - Ani Mardiantari; Rita Rahmawati (Bulletin of Indonesian Islamic Studies, 2024)
In doing business, Islam recommends complying with existing rules, including in terms of debt and credit (al-qardh), which aims as a form of mutual assistance. This study aims to analyze the practice of mosque cash fund accounts payable from the perspective of sharia economic law. This research uses a qualitative descriptive method, where data is obtained directly from the field and processed through qualitative analysis. The results showed that in the case of cash fund payables at the Roudlatul Jannah Mosque in Rama Oetama Village, Seputih Raman Sub-district, Central Lampung Regency, there is an agreement between the mosque cash management and the borrower regarding voluntary additions when returning funds. The amount of this addition is not specifically determined and is submitted according to the sincerity of the borrower. Based on the perspective of sharia economic law, the practice of cash fund payables is considered appropriate because it fulfills the principles of sharia, namely the principles of justice, ihsan, responsibility (al-mas'uliyah), sufficiency (al-kifayah), moderation (wasathiyah/i'tidal), as well as honesty and truthfulness that can be seen in the trustworthy management of mosque cash funds.